Substantive Ethics: Integrating Law and Ethics in Corporate Ethics Programs - Blodgett, Mark S. (2011)
Continual corporate malfeasance signals the need for obeying the law and for enhancing business ethics perspectives. Yet, the relationship between law and ethics and its integrative role in defining values are often unclear. While integrity-based ethics programs emphasize ethics values more than law or compliance, viewing ethics as being integrated with law may enhance understanding of an organization’s core values. The author refers to this integration of law and ethics as “substantive ethics,” analogous to the substantive law that evolves over time, which is applied to ethical breaches and carries sanctions for non-compliance. This article describes the integration of law and ethics as a mid-point between two polar views that define law and ethics either as having no relation or as being one and the same. Since corporations expressly state which laws they follow, a sample of corporate compliance statements is used to demonstrate this integrative mid-point. The sample also reveals that corporate ethics codes rarely express ethics and law as being integrated per se. Therefore, the author creates an example of a securities law compliance statement that is introduced with an integrative perspective of law and ethics. Perhaps such revised corporate codes will encourage corporate respect for both law and ethics and enhance ethical sustainability.
Keywords: Substantive ethics; Integrity-based corporate ethics programs; Ethical sustainability; Corporate ethics codes; Core Values; Business ethics and law